TANGGAP PERTUMBUHAN DAN PRODUKSI PADI GOGO VARIETAS SITU BAGENDIT TERHADAP PENGOLAHAN TANAH DAN FREKUENSI PENYIANGAN YANG BERBEDA - Fadli Heriadi Nasution; Jonathan Ginting; Balonggu Siagian (Universitas Sumatera Utara, 2013)
This research is proposed to find out the response of growth and yield of paddy rice situ bagendit variety by tillage of land ground and frequency of weeding. It was conducted at Dinas Pertanian UPT BBI, Tanjung Selamat with a height of 57 m above sea level on March until June 2012 with the soil which has ever tillage before, by using a Randomized Block Design of two factors, they are tillage of land ground (no tillage, two tillage and three tillage) and frequency of weeding (weeding 7 day, 14 day, 21 day and weeding full). The parameters observed were plant’s height, numbers of tiller, numbers of panicle, percentage shell of empty rice, number shell of rice containt, production shell of rice contain, 1000 grain weight, production shell of plot weight dry root and weight dry paddy stem. The results showed that tillage of land ground and frequency of weeding showed significant effects on plant’s height of 6 MST, numbers of tiller of 4 MST, numbers of tiller of 8 MST, percentage shell of empty rice, weight dry root and weight dry paddy stem. Key words : paddy rice, soil tillage , weeding